La polémica entre Voltaire y La Beaumelle: a propósito del "Supplément au Siècle de Louis XIV" - Ratto, Adrián (Montesquieu.it, 2018)
The aim of this paper is to examine the extent of the critiques that La Beaumelle gives to Voltaire in the annotated edition of the Siècle de Louis XIV, published in 1753, and his response in the Supplément au Siècle de Louis XIV, published a few months later. This, on the other hand, sheds some light on a number of tensions in the Voltaire’s historiographical project. It is shown that in the historical and historiographical works of the philosopher, there are different methodology criteria and that the joint between them is problematic.